ETIKA SOSIAL BUDDHISME DALAM KITAB SUTTA PITAKA (Kajian Filsafat) (Sanjiwani: Jurnal Filsafat, 2022)
Human ethics and morality have experienced a decline. This decline can be seen from the rise of cases of crime and conflicts that occur in the social environment of the community. Therefore, humans need religion as an aspect that guides humans in behaving. All religions actually teach the truth, including Buddhism. The teachings in Buddhism are dominated by ethics, which are broadly contained in the Sutta Pitaka. In this study, there are three formulations of the problem, including: (1) What is the essence of Buddhism in the Sutta Pitaka? (2) How is the social ethics of Buddhism in the Sutta Pitaka? (3)What is the meaning of Buddhist philosophy in the Sutta Pitaka? This study use three theories namely, hermeneutic theory, ethical theory and value theory. This type of research is qualitative. Data were collected using observation, interview, documentation, and library research. Then presented using the techniques of presenting the results of data analysis informally. Based on the result of this study indicate that: (1) Buddhist teachings in the Sutta Pitaka can be broadly understood through the teachings of Tiratana, Dukkha, and Kamma, which in essence these teachings emphasize ethics. (2) When viewed from the aspect of social ethics, Buddhist ethics can be classified in to three parts namely, theological ethics, ethics of self-development, and ethics of virtue. (3) The philosophical meaning of Tiratana, Dukkha, Kamma, Sila, Meditation teachings, and The Noble Eightfold Path always function as a guide for humans to be free from suffering and reach the Nibbana.